Left atrial appendage closure using Amulet device in a patient with prior percutaneous atrial septal defect closure - Cem Çöteli; Uğur Canpolat; Ergün Barış Kaya; Mehmet Levent Şahiner; Kudret Aytemir (KARE Publishing, 2018)
Percutaneous left atrial appendage (LAA) occlusion is an alternative therapeutic option for stroke prevention in patients with atrial fibrillation and contraindications for oral anticoagulation. There are few data available regarding the technical success of percutaneous LAA closure in patients with the previous implantation of an atrial septal defect (ASD) or a patent foramen ovale closure device. This is the description of a case of a successful LAA closure performed with an Amplatzer Amulet occluder device (St. Jude Medical, Inc., St. Paul, MN, USA) in a patient with a previous history of percutaneous ASD.